Scientific Inquiry and the Impact on Classroom Environment (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2018)
Scientific inquiry is an instructional strategy that requires students to engage in scientific problem solving by identifying a problem, designing an investigation, and supporting conclusions with evidence. The demand for the use of inquiry in the classroom is shown by the number of national and state standards that include inquiry as a requirement. Depending on the topic, inquiry in the classroom can range from structured to open. A classroom that engages in scientific inquiry creates an environment where students feel confident taking risks, collaborating, supporting conclusions with evidence and considering different positions. This article examines the foundations of scientific inquiry and the benefits to learners who are in a classroom where it is used.